Assessment of Social Media Needs for HIV Prevention Among Adolescents in Semarang City, Indonesia - Herdanindita, Erdelia; Zahroh Shaluhiyah; Antono Suryoputro (Universitas Airlangga, 2025)
Background: HIV remains a global health issue, with 1.65 million adolescents affected worldwide. In Indonesia, HIV cases continue to rise, especially among youth. In Semarang, adolescent knowledge about HIV is still low. Given their high use of digital media, developing youth-friendly social media content is essential to improve HIV prevention and education. Methods: This study applied a mixed-methods strategy with an explanatory sequential design. The quantitative phase involved collecting data through an online questionnaire using Google Forms, targeting 211 adolescents aged 16 to 18 years in Sub-district X, Semarang City. For the qualitative phase, in-depth interviews were conducted with one adolescent engaging in risky sexual behavior, a counselor from the Central Java Provincial National Anti-Narcotics Agency, and a counselor from a drug rehabilitation center in Semarang City. All data were examined using content analysis. Results: The study involved 211 adolescents aged 16–18 in Semarang. Only six reported having had sexual intercourse, most without consistent condom use. None reported injecting drug use. While most adolescents had received HIV information from teachers or health workers, they preferred online platforms like Instagram. Many had misconceptions about HIV transmission, such as believing it can spread through kissing or mosquito bites. Adolescents showed more concern about pregnancy than HIV and considered sex a taboo topic. Most preferred short, creative videos, especially podcasts and humorous content, with maximum duration of 45 seconds. Preferred topics included HIV basics, mental health, prevention, healthy relationships, and stories of people living with HIV. These findings support the development of youth-friendly social media content for HIV education.. Conclusion: Adolescents prefer learning about HIV through engaging social media content, especially short videos and podcasts. Despite some basic knowledge, misconceptions remain, and sexual health is still a sensitive topic. These findings highlight the need for youth-friendly digital content to improve HIV prevention.